Tiroid hastalıklarında nörofisyolojik değişikliklerin saptanması - Somay, Göksel (My University, 2003)
Bu çalışmanın amacı, çeşitli etyolojik nedenler ile hipertiroidi ve hipotiroidi tanısı almış hastalarda nöromusküler semptom ve bulguları değerlendirmektir. Hastalar klinik ve elektrofizyolojik testler ile değerlendirilmiştir. Çalışmaya 21 hipertiroidi, 19 hipotiroidi hasta ile yaş ve cinsiyet açısından eşleştirilmiş üst ekstremite için 29, alt ekstremite için 58 sağlıklı birey kontrol grubu olarak alınmıştır. Motor sinirlerin distal latansı, birleşik kas aksiyon potansiyel (BKAP) amplütüdü ve sinir ileti hızı, duysal sinir distal latansı, duysal sinir aksiyon potansiyel amplütüdü ve duysal ileti hızı, minimal F-dalga latansı, H-refleksi latansı ve iğne elektromiyografisi ile motor ünit aksiyon potansiyelleri (MÜAP) değerlendirilmiştir. Hipotiroidi hasta grubunda median motor distal latans uzaması (p<0.0001), median duysal distal latans uzaması (p<0.0001), median duysal aksiyon potansiyel amplütüd azalması (p<0.01) ve duysal ileti hızı yavaşlaması (p<0.01) kontrol grubuna göre anlamlı olarak farklı idi. Hipertiroidi hasta grubunda ise üst ekstremitede sadece median duysal aksiyon potansiyel amplütüdü azalması ve distal latans uzaması (p<0.05) belirgin idi. Alt ekstremitelerde ise bilateral peroneal sinir bilek- fibula başı ileti hızı yavaşlaması (p<0.0001), peroneal F-dalga latans uzaması (p<0.01), bilateral tibial sinir malleol üstü-popliteal fossa ileti hızı yavaşlaması (p<0.05), tibial F-dalga latans uzaması (p<0.01), sural sinir distal latans uzaması (p<0.0001) ve sural duysal aksiyon potansiyel amplütüd azalması (p<0.05) kontrol grubuna göre anlamlı olarak farklı bulunmuştur.Tiroid hastalarında, mononöropati ve polinöropati 17 ( %42.5) hastada (9'u hipotiroid, 8'i hipertiroid) saptanmıştır. Bu nöropatilerin %30'unu tuzak nöropatileri , %10'unu yaygın nöropatiler oluşturmakta idi. Bir ( %2.5) hastada bilateral sural duysal aksiyon potansiyeli elde edilememiştir. İğne EMG'sinde 2 hastada miyopati bulguları saptanmıştır. NEUROPHYSIOLOGIC ALTERATIONS IN THYROID DISEASES

With this study, it has been intended to evaluate the neuromuscular symptoms and findings observed in the patients specified with the diagnosis of hyperthyroidism and hypothyroidism induced by various etiologic reasons. This study included 21 patients of hyperthyroidism, 19 patients of hypothyroidism and a control group composed of 29 healthy persons for upper extremities and 58 healthy persons for lower extremities matches in respect of age and gender. The distal latency of the motor nerves, the compound muscle action potential (CMAP) amplitude and the motor nerve conduction velocities (NCVs), the sensory nerve distal latency, the sensory nerve action potential amplitude (SNAP) and sensory nerve conduction velocity, the minimal F-wave latency and H-reflex were evaluated. We also investigated motor unit action potentials (MUAP) by means of needle electromyography process. In patient group of hypothyroidism, the increase in the median motor distal latency (p<0.0001), the prolangation in the median sensorial distal latency (p<0.0001), the reduction in the median sensory action potential amplitude (SNAP) (p<0.01) and the slow in the velocity of nerve conduction (NCVs) (p<0.01) were found significantly different when compare to the control group. In patient group of hyperthyroidism, diminished median SNAP amplitude and the prolanged distal latency (p<0.05) were significant in the upper extremities. As for the lower extremities, the slow NCV in bilateral velocity of the nerve peroneal nerves wrist-fibula ending (p<0.0001), the prolanged peroneal F-wave latency (p<0.01), slowed NCVs in bilateral tibial nerve around malleolus-popliteal fossa (p<0.05), the prolanged tibial F-wave latency (p<0.01), sural nerve distal latency (p<0.0001) and the diminished sural nerve sensory action potential amplitude (p<0.05) were determined significantly different compare to the control group. Among the thyroid patients, 17 (42.5%) patients (9 with hypothyroidism and 8 with hyperthyroidism) were specified with the diagnosis of mononeuropathy and polyneuropathy. Entrapment neuropathy was observed in 30% and diffused neuropathy was observed in 10% of the patients. The bilateral sural nerve action potentials were absent in one of the cases (2.5%). Mypopathy findings were observed in 2 patients in needle EMG procedure.
Keywords: Hastalıklar; iç salgı yapıcı sistemler hastalıkları; Kan yapıcı; lenfatik; Nöroloji; Teknoloji (Uygulamalı bilimler); Tıp bilimleri; Tiroid ve paratiroid bezi hastalıkları